An analysis of the health system modernization processes in Russia and the results of their impact on the quality of medical services - Yu. Yu. Shvets (Путеводитель предпринимателя)
The article investigates the approved and implemented by the country’s health system modernization program. Analyzed the results of the program, its impact on the quality and accessibility of medical care to the population. Characterizing the main achievements and challenges of modernization, designated in the process of implementation of the programs approved by the Government, both at the federal and regional levels. The study provides recommendations for the development of the health system, the main directions of improving the quality and accessibility of health care. Forecast further steps to modernize the country ’s healthcare system.